O processo de indexação no contexto de uma biblioteca multinível - Silva, Alexandre Barbosa da (Brasil, 2024)
In this research, the general objective was to understand the procedures used in the indexing process in a multi-level library. For this purpose, three specific objectives were outlined, namely: a) to verify the administrative criteria adopted by a multi-level library in indexing; b) to identify the technical criteria adopted by a multi-level library in indexing; and c) to point out the relevance of adopting an indexing policy in a multi-level library. To achieve the established objectives, exploratory, descriptive, bibliographic, documentary, field research was conducted, with a qualitative approach. The sample was the Library of the Federal Institute of Amazonas - Manaus Center Campus, with the librarian coordinator of the organization as the subject or participant in the research. The data collection instrument was developed through a guide for conducting a semi-structured interview. It was concluded that the library faces a hindrance with the software used to manage the library, preventing indexing from taking place, and there are no defined technical criteria for its implementation, which reflects the absence of an indexing policy.